Nejistoty přesných délkových měření - Šrámek, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2008)
Diplomová práce má za úkol seznámit čtenáře, který se zajímá o problematiku nejistot délko-vých měření, s praktickou stránkou řešení těchto nejistot u jednoho velmi často používaného kalibračního postupu měření na délkoměru SIP. Toto měření bylo realizováno na půdě Českého metrologického institutu, kde autor pracuje, a tak mohl plně čerpat z množství vlastních zkušeností i zkušeností svých nadřízených a kolegů. Autor považuje národní metrologický orgán (ČMI) za dostatečnou záruku pro dále uváděné materiály, jak z hlediska odborné způsobilosti, tak i z hlediska formální korektnosti práce.

This diploma thesis is supposed to inform readers interested in the distance measurements un-certainty on practical issues connected with the solving of these troubles when utilising a frequently used calibration method - the SIP distance meter. This measuring was implemented by the Czech Metrologic Institute, where the author works; therefore he could take advantage of his rich experience as well as experience of his superiors and colleagues. The author regards the national metrological institute (ČMI) as a sufficient guarantee for the hereinafter presented materials, both regarding the professional qualification and from the perspective of formal rightness of this thesis.
Uncertainties of Accurate Length Measurement
Keywords: Metrologie; měření; měřicí přístroj; etalon; postup měření; výsledek měření; přesnost měření; nejistota měření; chyba měření; kalibrace; Metrology; measurement; measuring instrument; etalon (standard); measurement procedure; result of a measurement; accuracy of measurement; uncertainty of measurement; error of measure-ment; calibration